Portrayals of special educational needs in Norwegian ECEC psychoeducational reports: a document analysis in the context of inclusion - Kristiansen, Agnete; Uthus, Marit (Frontiers in Education, 2025)
IntroductionThis study aims to contribute to the ongoing debate on promoting more inclusive assessment practices for children in need of special educational support. It examines how special educational needs are portrayed in the assessment sections of psychoeducational reports (sakkyndige vurderinger) for children in Norwegian ECEC settings.MethodsA qualitative document analysis was conducted on selected psychoeducational reports, employing in-depth reflexive thematic analysis with a hermeneutic approach. The analysis focused on how the reports portrayed special educational needs and the extent to which they emphasized the individual child, the child’s social context, or both.ResultsSpecial educational needs were frequently framed in terms of the child’s limitations and deficits, often equated with their needs, and compared to the development of a “typical” child. Portrayals were sometimes ambiguous, influenced by individual differences, the dual role of the reports, and inconsistencies among stakeholders. While concerns were expressed about limited participation for some children, their own perspectives and needs within the broader social context were often absent.DiscussionPromoting inclusive assessment requires a holistic approach that addresses both the unique child’s special and basic psychological needs within their specific social environment. Incorporating children’s own perspectives seems crucial to identify opportunities and barriers for inclusion on both the individual and social level.